Evolutionary patterns of the SSU rRNA (V4 region) secondary structure in genus Euplotes (Ciliophora, Spirotrichea): insights into cryptic species and primitive traits - Wardani, Ratih Kusuma; Ahsan, Ragib; Shin, Mann Kyoon (PeerJ, 2025)
The genus Euplotes, a group of ciliated protists, has attracted attention as a model organism due to its widespread distribution and ease of cultivation. This study examines the evolutionary patterns of the SSU rRNA secondary structure within this genus, aiming to elucidate its role in supporting evolutionary relationships and uncovering cryptic species. By predicting the secondary structure of SSU rRNA and applying the CBC (Compensatory Base Change) concept analysis, we examined 69 species of the genus Euplotes, with 57 SSU rRNA gene sequences retrieved from GenBank and 12 newly sequenced specimens from South Korea. Our analysis revealed significant variations in the V4 region secondary structure, particularly in helix E23_8, across different clades of Euplotes. Reconstruction of the ancestral state indicated a transition from a simpler (Type I) to a more complex (Type II) secondary structure, with several species showing a reversal to Type I especially species in clade VI, suggesting of reverse evolution. In addition, our study identified cryptic species within Euplotes based on differences in the secondary structure of the V4 region, particularly evident in clade VI, where CBC analysis highlighted differences in E. minuta compared to E. vannus and E. crassus. These results highlight the utility of molecular data in refining species boundaries and evolutionary patterns within the genus Euplotes.
Keywords: Euplotes; V4 region; SSU rRNA; Secondary structure; Evolutionary pattern; Cryptic species; Primitive character